Influence of High Temperature on Seed Quality in Parental Lines of Rice Hybrids - HRISHIKESH SUTRADHAR; SK CHAKRABARTY; YOGENDRA SINGH (Seed Research, 2026)
A study was undertaken with the parental lines of three Indian rice hybrids viz., DRRH-2, DRRH-3and PRH-10 during Kharif 2012-13 at ICAR-Indian Agricultural Research Institute, New Delhi. Parental lines were sown in three different sowing dates during the month of April (1st sowing), May (2nd sowing) and June (3rd sowing) to expose the plants to different range of temperatures and to understand its effect on seed quality. Seed quality parameters such as per cent mean germination at final count (83%, 87% and 92% in 15, 2nd and 3rd sowing, respectively), mean seed vigour index 1 (1878.37, 2242.63 and 2591.98 in 1st, 2nd and 3rd sowing, respectively), mean seedling dry weight (9.5 mg, 10.1 mg and 10.7 mg in 1st, 2nd and 3rd sowing, respectively) and mean 1000 seed weight (17.95g, 18.67 and 19.18 g in 1st, 2nd and 3rd sowing, respectively) were significantly decreased by high temperature. It is concluded that higher temperature during seed development stage reduces the seed quality irrespective of genotypes.